2017
DOI: 10.18001/trs.3.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Recall of E-cigarette Advertisements and Adolescent E-cigarette Use

Abstract: Objective We examined the impact of e-cigarette advertising on e-cigarette use behaviors among youth over time. Methods At baseline, 3907 students participated in a youth tobacco surveillance study from 2014–2015 and 2488 students completed a 6-month follow-up. Weighted logistic regression models investigated the recall of e-cigarette advertisements (TV/radio/billboards/retail/Internet) as a risk factor for e-cigarette perceived harm, use, and susceptibility. Results The odds of ever e-cigarette use was 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…Exposure to EC advertising were associated with susceptibility to trying ECs, [ 28 , 29 , 51 , 52 ] and we further showed the AORs were similar when exposed to online and traditional broadcast media (Supplementary Table 1 ). Tobacco advertising in traditional media are increasingly banned globally.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Exposure to EC advertising were associated with susceptibility to trying ECs, [ 28 , 29 , 51 , 52 ] and we further showed the AORs were similar when exposed to online and traditional broadcast media (Supplementary Table 1 ). Tobacco advertising in traditional media are increasingly banned globally.…”
Section: Discussionsupporting
confidence: 52%
“…Cohort studies have reported that adolescents exposed to online tobacco marketing were more likely to initiate tobacco use and progress to poly-tobacco use [ 27 ]; those who recalled EC advertisements at baseline were 77% more likely to be susceptible to EC use (adjusted odds ratio [AOR] = 1.77, 95% confidence interval [CI] 1.20–2.61) and twice more likely to use ECs (2.99, 1.50–5.97) within 6 months [ 28 ]. A randomised controlled trial (RCT) showed that exposure to EC advertising increased curiosity to try ECs (2.85, 1.07–7.61) in young adults who had never used cigarettes or ECs [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“… 41 Annual smokeless tobacco marketing expenditures nearly doubled from 2002 ($235 million) to 2010 ($444 million) and remained steady through 2014. 12 This widespread marketing exposure has been linked to increased product awareness 42 and product use 16 , 43 among adolescents. Furthermore, promotional tactics for these products have specifically targeted existing tobacco users.…”
Section: Discussionmentioning
confidence: 99%
“…Youth were asked how often they recalled seeing ads or promotions for tobacco products in four contexts: online, in newspapers or magazines, outdoors and in stores [39]. Categorical responses were recoded (‘never’, 0; ‘rarely/sometimes,’ (1); ‘most of the time/always’, (2); and summed across the four questions, creating a linear index (range = 0–8) measuring cumulative exposure to tobacco ads [3,40].…”
Section: Methodsmentioning
confidence: 99%